Positive association between chronic hepatitis B virus infection and anemia in pregnancy in Southern China - Renliang Huang; Zhe Lu; Xinze Li; Duo Zhou; Jing Xu; Dan Lin; Yunxue Fu; Yan Liang; Xuexia Li; Frank Petersen; Qiaomiao Zhou; Xinhua Yu (Scientific Reports)
Abstract This observational investigation aimed to explore potential risk factors for anemia in pregnancy. Firstly, a cross-sectional study was conducted, encompassing a review of clinical data of 43,201 pregnant women admitted to the Hainan Women and Children’s Medical Center between January 2017 and December 2020. Comparison between women with and without anemia in pregnancy revealed significant differences between the two groups concerning age, gestational diabetes, hypothyroidism, hyperthyroidism, chronic hepatitis B virus infection, syphilis infection, and human immunodeficiency virus infection. Multivariable logistic regression analysis showed that chronic hepatitis B virus infection was significantly associated with anemia during pregnancy (AOR   2.97, 95% CI 2.57–3.44, p < 0.0001). Subsequently, a retrospective cohort comprising 86 cases with chronic hepatitis B virus infection and 129 control subjects recruited from the Hainan Women and Children’s Medical Center from November 2021 and January 2023 was examined. Results of the examination revealed a corroborative association between chronic hepatitis B virus infection and anemia in pregnancy (OR  2.13, 95% CI 1.20–3.79, p = 0.0092), particularly manifesting in the third trimester of gestation. Further analysis unveiled distinctive hematological alterations among cases with chronic hepatitis B virus infection, characterized by diminished erythrocyte size and reduced levels of corpuscular hemoglobin. Collectively, these findings underscore a positive association of chronic hepatitis B virus infection with anemia during pregnancy.